UNSUR TINDAK PIDANA DAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PENYEBARAN GAMBAR PORNOGRAFI: Elements Of Criminal action And Criminal Sanctions Against Person Of The Criminal Action Of Electronic Pornography Images) - Davita, Bunga; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
Currently the world is increasingly connected to each other, pornography can be freely accessed without any restrictions by irresponsible parties. This ultimately has an impact on changes in values, moral norms, and decency, so the author will examine and discuss cases of distributing pornographic images electronically based on the Payakumbuh District Court Decision Number 4/Pid.Sus/2022/PN Pyh. So the formulation of the problem in this study is: is there a compatibility between the Defendant's actions and the provisions of Article 27 (1) of the ITE Law and whether it can be prosecuted based on Article 27 paragraph (1) ) of the ITE Law. This study uses normative legal research methods using secondary data consisting of primary, secondary and tertiary. The nature of this research is descriptive. then analyzed qualitatively. draw conclusions with the deductive method. Based on the analysis carried out, a link was achieved between the act and the provisions of Article 27 paragraph (1) of the ITE Law, so that the judge's acquittal against the defense was inappropriate. does not fulfill a sense of justice and sanctions should be based on the provisions of Article 45 paragraph (1) in conjunction with Article 27 paragraph (1) of the ITE Law